Nonmuscle Myosin Heavy Chain ⅡA-Mediated Exosome Release via Regulation of the Rho-Associated Kinase 1/Myosin Light Chains/Actin Pathway - Yanni Lv; Jin Chen; Jinfang Hu; Yisong Qian; Ying Kong; Longsheng Fu (Frontiers Media S.A., 2020)
Nonmuscle myosin ⅡA, a kind of ATP-dependent molecular motor, binds actin to form the molecular motors of the cell. We found that interfering with nonmuscle myosin heavy chain (NMMHC) ⅡA could affect the exosome release from microglial cells stimulated by LPS. LPS could enhance exosome release from microglial cells by increasing exosome concentration, elevating the rate of positively labeled CD9 and CD81 proteins and protein expression. The myosin inhibitor, blebbistatin, could decrease the concentration of released exosome and reduce CD9 and CD81 protein expression on the exosome surface compared with that in the LPS group. To further determine the exact subtype of myosin Ⅱ responsible for these effects, we transfected microglial cells with siRNA for MYH9, MYH10, and MYH14. The data showed that only the transfection of siRNA-MYH9, but not MYH10 or MYH14 could decrease the released exosome concentration and particle size compared with those in the LPS group. siRNA-MYH9 would also weaken the CD9 and CD81 protein positive rate and protein expression compared with that in the LPS group by the quantification of CD9 and CD81 fluorescence intensities and by western blotting. Western blots and immunofluorescence assays indicated that NMMHC ⅡA might trigger the ROCK1/MLC/actin signaling pathway of microglial cells upon stimulation by LPS, which might be the potential mechanism of exosome release. These observations demonstrated that NMMHC ⅡA might be the potential target required for exosome release.